Preventing sexual violence in sport: Determinants of positive coach-bystander behavior - Verhelle, Helena; Vertommen, Tine; Peters, Gjalt-Jorn Ygram (Frontiers in Psychology, 2022)
Coaches are instrumental in creating safe sport environments, especially in preventing sexual violence, but little is known about helpful bystander behaviors, hampering effective prevention programs. To identify determining characteristics of bystander behavior, 1442 Belgian youth-sport coaches completed an online questionnaire on bystander-related attitudes, norms, autonomy beliefs, and self-efficacy. Experiential attitude expectation, instrumental attitude evaluation, perceived referent behavior and approval, and subskill presence were positively associated with coaches’ intentions to intervene. Of the determinants of positive coach-bystander behavior, attitude and perceived norms proved key constituents for programs addressing sexual violence in youth sport. To promote active coach-bystander behaviors, the results are discussed from a theoretical and practice-oriented perspective.